1989
DOI: 10.1159/000132863
|View full text |Cite
|
Sign up to set email alerts
|

Trisomy 7 and sex chromosome loss in human brain tissue

Abstract: Short-term cultures of nonneoplastic brain tissue from 11 patients, seven of whom had a malignant brain tumor, were cytogenetically examined. In only a single case was a wholly normal chromosome complement detected; the remaining ten cases exhibited mosaicism with clonal numerical aberrations found alongside cells carrying a normal karyotype. The abnormal clones were characterized by trisomy 7, the loss of the Y chromosome in men and an X chromosome in women, or by combinations thereof. No structural aberratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
60
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(64 citation statements)
references
References 8 publications
4
60
0
Order By: Relevance
“…Chromosome 7 gain is a common finding in several benign and malignant neoplasms, as well as in non-neoplastic lesions and apparently normal tissue (Heim et al, 1989;Bardi et al, 1992;Mitelman et al, 2007). While it has been suggested that this gain may represent a primary and pathogenetically-important abnormality in some solid tumors, it is often regarded as a common secondary change and may be associated with disease progression (Johansson et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Chromosome 7 gain is a common finding in several benign and malignant neoplasms, as well as in non-neoplastic lesions and apparently normal tissue (Heim et al, 1989;Bardi et al, 1992;Mitelman et al, 2007). While it has been suggested that this gain may represent a primary and pathogenetically-important abnormality in some solid tumors, it is often regarded as a common secondary change and may be associated with disease progression (Johansson et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Although such a variability could be related partially to the small number of cases analyzed in many studies, it might also be due to the use of different methods for the detection of specific genetic abnormalities. Accordingly, conventional cytogenetics, which have been used in most studies, have been shown to have several limitations related to the fact that tumoral metaphases (32) are required. These include the potential existence of clonal selection during cell culture, the analysis of a small fraction (typically Ӎ1%) of all the cells present in the tumor sample, and the difficulties in obtaining tumor cell metaphases in a significant proportion of cases.…”
mentioning
confidence: 99%
“…It is less frequently observed in lymphomas and is very infrequently observed in leukemias. The finding of trisomy 7 in nonneoplastic tissues from patients with lung, kidney, or brain tumor by conventional cytogenetic analysis (CCA) on short-term cultures raised the question whether these cells carrying an extra chromosome 7 reflect the presence of (pre)malignant cells, a culture-induced artefact, or, perhaps, an in vivo organ mosaicism (3)(4)(5)(6).…”
mentioning
confidence: 99%